STRENGTHENING MUTUAL COOPERATION FOR PANCASILA STUDENTS THROUGH MARTIAL ARTS LEARNING - Sofiatunnisa, Dian; Supriyadi, Tedi; Suherman, Ayi (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This research highlights the urgency of instilling the value of mutual cooperation from an early age to build togetherness in social life. The aim is to develop students' mutual cooperation character through pencak silat supported by pop-up media as a learning tool. This research uses a 4D model, namely problem definition, intervention design, learning material development, and dissemination of results. A mixed method approach was applied to understand the effectiveness of learning pencak silat in forming the character of mutual cooperation. The research subjects involved 30 students of Madrasah Ibtidaiyah Tarunajaya. Research instruments in the form of questionnaires, observations and documentation are used to measure student character development. Quantitative data was analyzed using a paired sample t-test, while qualitative data was analyzed using a thematic approach. The results showed that pop-up video media significantly increased students' mutual cooperation scores, with the average score increasing from 9.1 to 16.0 (75.82%). The paired sample t-test showed p < 0.000, and the n-gain analysis averaged 0.68 indicating moderate to high effectiveness. Observations also show increased social interaction and cooperation. In conclusion, this approach is relevant to the Pancasila student profile in building solidarity and cooperation.